LITERASI KEUANGAN DAN PENGARUHNYA TERHADAP KINERJA UMKM BATIK TULIS LASEM - Wulan Suryandani; Hetty Muniroh (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
Financial literacy is seen as an important instrument for the success of MSMEs, because it helps to understand and evaluate the information needed to make daily decisions that have a financial impact in daily company management. Improving the performance of MSMEs needs to be studied further to discuss, because MSMEs have an important role in a country’s finance. However by increasing knowledge about financial literacy it is difficult for MSMEs to improve their performance. The purpose of this study is to know the financial influence on the performance of the MSMEs Batik Tulis Lasem. The analysis technique uses simple linier regression. The result of this study show that financial literacy have positive and not significant effect on MSME performance, this caused by many things. MSME performance can affect many things and financial literacy according to the results of research in MSMe Batik Tulis Lasem is not a major factor affecting significant to performance. It can be predicted that according to respondents written by Batik Tulis Lasem, the performance of MSMEs can be supported by things other than financial literacy such as producyion and operational factors, human resource capabilities (HR) or also by marketing of the products.